If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(c + 3) = 7 + 5c Reorder the terms: 6(3 + c) = 7 + 5c (3 * 6 + c * 6) = 7 + 5c (18 + 6c) = 7 + 5c Solving 18 + 6c = 7 + 5c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-5c' to each side of the equation. 18 + 6c + -5c = 7 + 5c + -5c Combine like terms: 6c + -5c = 1c 18 + 1c = 7 + 5c + -5c Combine like terms: 5c + -5c = 0 18 + 1c = 7 + 0 18 + 1c = 7 Add '-18' to each side of the equation. 18 + -18 + 1c = 7 + -18 Combine like terms: 18 + -18 = 0 0 + 1c = 7 + -18 1c = 7 + -18 Combine like terms: 7 + -18 = -11 1c = -11 Divide each side by '1'. c = -11 Simplifying c = -11
| 2t^2+8=6t | | (3-u)(5u+2)=0 | | (2x+1)2=10x-1 | | -5(x-2)=3(x+2) | | 2(x-3)=5(2x+3)+3 | | 4=5(v+4)-7v | | 13x-43= | | 90+x+23+x+13=180 | | x+3.6=2.4 | | 2=x+3-5x | | 36=n-20 | | x+9y=68 | | 17=3+31t-16t^2 | | 2(x-3)2=8 | | X^2=4x-2 | | 8x+15-7x=-5-12 | | -8*-2= | | 4x-11=29 | | 8+y=-9 | | -4(x+1)-17=10+5 | | 5n+35=55 | | 1.9+1.3x=23.7x | | x^2+14x+49=-14 | | 8x+5+9=3 | | x^2+14x+63=0 | | 8x^6-56x^5+40x^4= | | -2p+7=-(5p+1) | | 6=z+12 | | 2x-9+2x+4=180 | | 4w-16=4(w-4) | | -2y-13=-5y-10 | | -1-9=3x+2-2x |